1"Etika dan Representasi dalam Film Dokumenter: Tantangan Dokumentaris di Era Post-Truth Tahun 2024" - Melati Kusuma Wardhani, S.I.Kom, M.I.Kom, Melati Kusuma Wardhani, S.I.Kom, M.I.Kom (Profilm Jurnal Ilmiah Ilmu Perfilman dan Pertelevisian, 2024)
In the post-truth era, where the lines between facts and opinions are often blurred, documentaries face great challenges in maintaining narrative integrity, especially when presenting controversial or sensitive issues. The study explores how documentaries can navigate these challenges bymaintaining a balance between compelling facts and narratives, verifying information thoroughly, and using cinematic techniques wisely to avoid emotional manipulation. The study also discusses the importance of transparency in the production process and the ethical responsibility ofdocumentaries in preventing polarization and the spread of misinformation. Through a qualitative approach, the study analyzes relevant documentary film examples, such as "The Social Dilemma" and "Leaving Neverland," to identify best practices in maintaining credibility and honesty in documentary narratives in the post-truth era.